Implications of the Protestant work ethic for cooperative and mixed-motive teams. (February 2014) - Townsend, Sarah S. M.; Thompson, Leigh L.
The investigation of teams and teamwork in cooperative (e.g., group brainstorming and team decision-making) and mixed-motive (e.g., negotiation) contexts has been carried out through a variety of lenses and disciplines. One lens that has not been used to rigorously theorize about and empirically investigate teams is that of ideologies. In this review, we juxtapose the study of a particular status-related ideology, the Protestant work ethic (PWE), in cooperative and mixed-motive contexts. We begin with an analysis of PWE, and then discuss 3 sets of empirical findings. In particular, we consider the association of PWE with (a) motivational orientations; (b) greater perceptions of personal control; and (c) justification of status differences. Given these associations, we theorize how PWE might affect cooperative and mixed-motive teamwork, suggesting that PWE will exert largely positive effects among cooperative teams, but will produce more varied effects among mixed-motive teams.